Revenue collapses and the consumption of small business owners in the COVID-19 pandemic - Kim, Olivia S.; Parker, Jonathan A.; Schoar, Antoinette (Journal of Financial Economics, 2025)
Using financial account data linking small businesses to their owner households, we examine how business owners’ consumption responded to changes in business revenues during the COVID-19 crisis. In the first two months following the National Emergency, business revenues declined by 40 percent, largely driven by national factors rather than local infection rates or policies. However, the pass-through of revenue losses to owner consumption was limited: each dollar of revenue loss resulted in only a 1.6-cent decline in consumption. This muted pass-through persisted through 2021, even after the introduction of COVID-19 vaccines. Our findings suggest that federal subsidies and pandemic-induced reductions in spending opportunities explain the limited impact.